Rancang Bangun Sistem Informasi Penjualan Biji kopi pada Mr. Coffee Surabaya - Hutagalung, Ika Widyasari; Setyawan, Henry Bambang; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Mr. Coffee is a coffee field sales business that began to develop in 2013. At the current sales process owners can’t perform recording sales precisely because poorly supported by adequate information coffee sales lead to errors in the recording of sales, so the impact on stock control materials raw coffee warehouse that often have out of stock of coffee which ordered the customer, and the customer who still has a receivable purchase coffee on previous transactions. So may result in losses for the parties Mr. Coffee.Based on this problem, then created a web-based sales information system that can help provide information about the registration of the sale of coffee, coffee stock management of raw materials using methods Reorder Point (ROP), and the management of customer receivables.Based on the results of the implementation and evaluation of the system, recording sales on Mr. Coffee-based website is to provide information for the company to make record sales of coffee, coffee raw material stock control in the barn, and the recording of customer receivables on previous transactions.